Behavioral Changes In Contraceptive Use Among Women Of Reproductive Age With Unmet Needs Following Family Planning Counseling - Ulandari, Ida Ayu Desy; Wirata, I Nyoman; Suindri, Ni Nyoman (Jurnal Riset Kesehatan, 2024)
The low participation of women of childbearing age in participating in family planning services has led to an increase in the incidence of unmet need in Indonesia. This research aims to determine the differences in knowledge, attitudes, and decision-making in women of childbearing age who have unmet needs before and after being given family planning counseling in the working area of the UPTD Puskesmas Tabanan III. This research uses a pre-experimental research design. The sample for this research is women of childbearing age (WUS) with unmet needs in the UPTD Puskesmas Tabanan III sample of 40 people. The data was then analyzed univariately and bivariately using the Wilcoxon test. The results show that there are differences in knowledge, attitudes, and decision-making in women of childbearing age who have unmet needs before and after being given family planning counseling. It is hoped that health workers will maintain and improve the quality of providing family planning services to the community.